Bidirectional Relationship Between Diabetes and Acute Pancreatitis: A Population-Based Cohort Study in Taiwan. Issue 2 (January 2016) - Lee, Yi-Kung; Huang, Ming-Yuan; Hsu, Chen-Yang; Su, Yung-Cheng
Abstract : Abstract: The proposed bidirectional relationship between acute pancreatitis (AP) and diabetes has never been examined with the same source of data. Furthermore, the effects of disease severity on this relationship have not been fully evaluated. The present study employed the findings from a single database to measure the strength of the association between AP and diabetes. Findings from 1 million National Health Insurance beneficiaries were utilized. Two cohort studies with this database were selected to evaluate the linkage between diabetes and AP. The first cohort analysis addressed the risk of AP among diabetic patients and was comprised of 42, 080 diabetic patients and 672, 146 unexposed subjects. The second cohort analysis considered the risk of diabetes among patients with AP and enrolled 3187 patients with AP and 709259 unexposed subjects. All adult beneficiaries were followed from January 1, 2005 to December 31, 2012 to identify outcomes of interest. Cox regression models were applied to compare hazards adjusted for potential confounders. For the first cohort, the adjusted hazard ratio (HR) of AP was significantly increased by the presence of diabetes (1.72; 95% confidence interval [CI], 1.52–1.96). In diabetic patients with a history of hyperglycemic crisis episodes (HCEs), the HR was even higher (6.32; 95% CI, 4.54–8.81). For the second cohort, the adjusted HR of diabetes in patients with AP was increased compared to the general population (2.15; 95% CI, 1.92–2.41). For patients with severe AP, the HR was also higher (2.22; 95% CI, 1.50–3.29) but did not differ significantly from that for patients with nonsevere AP. The 2 cohort studies provided evidence for the bidirectional relationship between diabetes and AP. Moreover, diabetic patients with history of HCEs may be associated with higher risk of AP.